2021
DOI: 10.1017/jfm.2020.1173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spatial dimension on a model of fluid turbulence

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 66 publications
4
11
0
Order By: Relevance
“…Thus, any scaling anomalies seen in this work cannot be associated with intermittency corrections. We also note here that results from the EDQNM equation for second-and third-order statistical quantities are in good agreement with DNS measurements in three and four dimensions, as shown in Clark et al (2021b). As such, our work will focus on such quantities in determining the chaotic properties of higher-dimensional flows.…”
Section: Chaos and Predictability In Turbulencesupporting
confidence: 75%
See 4 more Smart Citations
“…Thus, any scaling anomalies seen in this work cannot be associated with intermittency corrections. We also note here that results from the EDQNM equation for second-and third-order statistical quantities are in good agreement with DNS measurements in three and four dimensions, as shown in Clark et al (2021b). As such, our work will focus on such quantities in determining the chaotic properties of higher-dimensional flows.…”
Section: Chaos and Predictability In Turbulencesupporting
confidence: 75%
“…In general, these closure-based methods do not account for intermittency and thus are not suited for studies in anomalous scaling. However, they are well suited for the study of low-order statistics in higher dimensions as was carried out in Clark et al (2021b) using the EDQNM closure (Orszag 1970). Here, it was found that the enstrophy production reaches a maximum near six dimensions.…”
Section: Numerical Studies Beyond Three Dimensionsmentioning
confidence: 99%
See 3 more Smart Citations